2016
DOI: 10.1093/brain/aww204
|View full text |Cite
|
Sign up to set email alerts
|

Ventral tegmental area deep brain stimulation in refractory short-lasting unilateral neuralgiform headache attacks

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…At median follow-up time of 29 months, 4 patients were rendered pain free for large amounts of time, and the response rate of at least 50% attack reduction was 82%. 57 Adverse events included mild incision site pain, subcutaneous displacement of the implantable pulse generator, transient oscillopsia, and minor wound infection. One patient required removal of the system due to wound infection.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…At median follow-up time of 29 months, 4 patients were rendered pain free for large amounts of time, and the response rate of at least 50% attack reduction was 82%. 57 Adverse events included mild incision site pain, subcutaneous displacement of the implantable pulse generator, transient oscillopsia, and minor wound infection. One patient required removal of the system due to wound infection.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…A series of 11 SUN patients who were refractory to multiple medical treatments, and did not respond to, or were denied, ONS, underwent DBS to the ventral tegmentum ipsilateral to the site of the pain. At median follow‐up time of 29 months, 4 patients were rendered pain free for large amounts of time, and the response rate of at least 50% attack reduction was 82% . Adverse events included mild incision site pain, subcutaneous displacement of the implantable pulse generator, transient oscillopsia, and minor wound infection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition there are positive reports on topiramate, carbamazepine, gabapanetin, botulinum toxin, and nerve blocks, which seemed to be effective in some patients . Invasive procedures used in patients refractory to pharmacological treatment include microvascular decompression, deep brain stimulation, and occipital nerve stimulation . In two small case series, microvascular decompression rendered seven of 12 patients pain‐free.…”
Section: Sunct/sunamentioning
confidence: 99%
“…In 11 patients, deep brain stimulation of the ventral tegmental area showed a 50% improvement in daily attack frequency in 82% of the patients and a reduction in headache load by 99%. The system had to be removed in one patient because of wound infection, otherwise there were no serious adverse events . Nevertheless, it is essential to weigh a potential benefit against the risk of serious complications .…”
Section: Sunct/sunamentioning
confidence: 99%
“…With respect to CCH, VTA‐DBS improved CCH attack frequency (reduction of 60%), provided a 30% decline in its intensity, and improved quality of life, disability, and mood disturbance after a median follow‐up of 18 months, as compared to baseline. A prospective study found a decline in the frequency (78%) and severity of SUNCT in 11 patients, with a responder rate (defined as at least 50% reduction in daily attack frequency) of 82% after 29 months of ipsilateral VTA‐DBS …”
mentioning
confidence: 99%